CUPID: a protocol of a randomised controlled trial to identify characteristics of similar Chinese patent medicines. Issue 11 (27th November 2014) - Cao, Hongbo; Zhai, Jingbo; Li, Nan; Cao, Hongxia; Lei, Xiang; Mu, Wei; Liu, Zhi; Wang, Hui; Shang, Hongcai
Abstract : Introduction: Traditional Chinese medicine (TCM) has accumulated some experience in curing stable angina pectoris (SAP) and efficacy has been demonstrated. Chinese patent medicines, known as modern dosage forms of TCM, can attain the desired effect in clinical application only with the guidance of TCM syndrome theory. However, due to their use by a large number of persons with little knowledge of TCM theories and practices, their efficacy and reputation have been seriously affected. Method and analysis: Two common syndrome types of SAP in TCM, 'qi deficiency and blood stasis' and 'qi stagnation and blood stasis', will be studied in 144 subjects from four TCM hospitals in Tianjin in China using a partial crossover design. The two syndromes will be broken down into six symptom combinations; patients will select a combination of the most distressing to them, and then will be randomised into two groups. Each group, on the basis of routine medication, will be administered one kind of Chinese patent drug: Qishenyiqi Dripping Pills or Compound Danshen Dripping Pills. The treatment characteristics of the two medicines will be evaluated with the COME-PIO method developed by our research team. Ethics and dissemination: This protocol has been approved by the medical ethics committee of Tianjin University of TCM (registration number TJUTCM-EC20130005). The study is safe and reliable. Trial registration number: Chinese clinical trials register ChiCTR-TTRCC-14004406.